2018
DOI: 10.1002/rcm.8199
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of in vitro metabolites of three tetrahydroprotoberberine alkaloids in rat liver S9 by high‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry

Abstract: This was the first ever investigation of in vitro metabolism of THB, THCP and THCB in rat liver S9 by using a sensitive and accurate HPLC/QqTOF-MS method. The tentatively proposed metabolic pathways of the three alkaloids will provide a basis for further studies of the in vivo metabolism of the three compounds in animals and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In general, it is difficult to identify the unknown constituents from mass spectra without information about the fragment ions and retention times. The fragmentation mechanism of Macleaya alkaloids can be summarized based on the findings of previous studies . Target profiling and identification of BIAs in the extracted samples from the fresh aerial parts of M. microcarpa were exclusively based on retention time (<0.25 min), exact mass (M + , [M + H] + , and [M + Na] + ions, mass error<10 ppm), and MS/MS product ions in a database of the accurate mass of known compounds and the mass spectral fragmentation behavior of Macleaya alkaloids.…”
Section: Resultsmentioning
confidence: 99%
“…In general, it is difficult to identify the unknown constituents from mass spectra without information about the fragment ions and retention times. The fragmentation mechanism of Macleaya alkaloids can be summarized based on the findings of previous studies . Target profiling and identification of BIAs in the extracted samples from the fresh aerial parts of M. microcarpa were exclusively based on retention time (<0.25 min), exact mass (M + , [M + H] + , and [M + Na] + ions, mass error<10 ppm), and MS/MS product ions in a database of the accurate mass of known compounds and the mass spectral fragmentation behavior of Macleaya alkaloids.…”
Section: Resultsmentioning
confidence: 99%
“…For M15, it was observed at the retention time of 27.20 min with [M+H] + ion at m/z 259.09727 Da (−1.94 ppm) and [M‐H] − ion at m/z 257.08211 Da (−0.70 ppm), and its molecular formula was temporarily predicted as C 15 H 14 O 4 . Referring to the related literature, its relative molecular weight was 2 Da (2H) higher than P12, which indicated that M15 was the hydrogenation metabolite of liquiritigenin [36, 37].…”
Section: Resultsmentioning
confidence: 99%